Yield analysis with situations - MOSKEWICZ MATTHEW W; LAM MICHAEL C; LAI YAIEH; GENNARI FRANK E; MCINTYRE GREGORY R (2010)
Systems, methodologies and technologies for the analysis and transformation of integrated circuit layouts using situations are disclosed. A method for transforming an integrated circuit (IC) layout includes recognizing shapes within the IC layout, identifying features for each of the shapes and extracting situations for the respective features. Extracted situations can be used to improve optical proximity correction (OPC) of the IC layout. This improved OPC includes extracting the situations, simulating the situations to determine a set of the situations identified for modification based on failing to satisfy a desired OPC tolerance level, modifying the set of situations to improve satisfaction of the desired OPC tolerance level, and reintegrating the modified set of situations into the IC layout. Extracted situations can also be used to improve aerial image simulation of the IC layout. This improved aerial image simulation includes extracting the situations, simulating a subset of the situations to determine aerial images of the subset, and tiling the subset of situations to form a larger aerial image. Extracted situations can further be used to improve density analysis of the IC layout. This improved density analysis includes extracting the situations for a window of the IC layout, removing overlap from the window based on the extracted situations, calculating a density for each of the situations, and calculating a density for the window based on the density for each of the situations.